1999
DOI: 10.1037/h0086831
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of treatment of depression: Medicalization or empowerment?

Abstract: An interview study was conducted in which women's experiences of diagnosis and treatment for depression were explored. Nine women who had been diagnosed by a physician participated in the study. Topics explored in the interview included how women came to be diagnosed as depressed, how treatment was experienced, how they understood the causes of their depression, and how being diagnosed had affected their view of themselves and their futures. Analysis involved a thematic approach guided by the topics addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 15 publications
1
39
1
1
Order By: Relevance
“…This finding is also different from the study by Gammel & Stoppard 26 where they found that 'younger' women in Canada were against taking medication and wanted to cope on their own as opposed to 'older' women. However, there may be a qualifier here where some respondents in the present study, while explicating benefits of taking medication, acknowledged the use of behavioral modification as a long term solution to their depression.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is also different from the study by Gammel & Stoppard 26 where they found that 'younger' women in Canada were against taking medication and wanted to cope on their own as opposed to 'older' women. However, there may be a qualifier here where some respondents in the present study, while explicating benefits of taking medication, acknowledged the use of behavioral modification as a long term solution to their depression.…”
Section: Discussioncontrasting
confidence: 99%
“…While a number of surveys have pointed to a preference for counselling over drug treatment for depression in general practice attenders and depressed primary care patients, 20,21 other research has reported on the medicalised accounts provided by depressed individuals, involving biomedical explanations and positive evaluations of antidepressant medication. 22 The present research contributes to the understanding of patient views on depression management by indicating the diversity of possible viewpoints, and the fluidity of these over time (as highlighted by Karp in his work on 'illness careers' in depression). 23,24 In line with the conclusions of previous qualitative studies on depression in primary care (for example, Gask et al 25 ), the present findings highlight the importance of patient and GP beliefs in influencing management.…”
Section: Comparison With Existing Literaturementioning
confidence: 73%
“…The experience of discussing depressive symptoms with one's health care provider is significant in individuals' cognitions of self and their conceptualization of depression and its causes (Rogers et al, 2001;Gammell & Stoppard, 1999;Wisdom & Green, 2004). Since the development of depression often includes sufferers' attempts to identify a cause for their symptoms (situational vs. organic), seeking treatment and directly addressing the issue may exacerbate the discomfort in both illness identity and the search for explanations (Estroff, Lachicotte, Illingsworth, & Johnston, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…While the topic has not been studied extensively in adolescents, adults tend to be suspicious of psychopharmacological treatment (Offer et al, 1991;Jorm et al, 2000) and believe it is counter to their goals of personal empowerment (Gammell & Stoppard, 1999). College-age young adults also express ambivalence about taking medication (Venarde, 1999), stating concerns about being stereotyped as a "person who takes antidepressants" and a dislike of feeling reliant on medication to feel better.…”
Section: Introductionmentioning
confidence: 99%